PENINGKATAN KEAMANAN TRANSMISI REAL TIME VIDEO SURVEILLANCE MENGGUNAKAN SECURE SOCKET LAYER - Iswahyudi, Catur; Pratama, Nanda Adi; Triyono, Joko (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Security is a very important aspect of data exchange. Usually, the data in video surveillance is transmitted only for certain parties. The data must accepted to entitled user with maintained confidentiality, and avoid from packet sniffing by others. Therefore, to secure the data in video surveillance, it needs a data encryption method to hide information.SSL (Secure Socket Layer) is reliable for securing a real-time data or video transmission. SSL can be implemented on a webserver that has public hosting. In this study, Zoneminder video surveillance system implemented on the web server, then SSL will encrypt the transmitted data between the Zoneminder server and the client.The results shows that surveillance videos protected by SSL, safe from packet sniffing actions and no degradation on QoS and video quality.